2013
DOI: 10.1186/1749-8090-8-86
|View full text |Cite
|
Sign up to set email alerts
|

Extraanatomical coronary artery bypass grafting in patients with severely atherosclerotic (Porcelain) aorta

Abstract: BackgroundCannulation, cross clamping, or partial clamping of the aorta during a proximal anastomosis may cause embolic complications in patients with severely atherosclerotic (porcelain) aortas. These patients carry high morbidity and mortality risks due to intraoperative atheroembolism.MethodsBetween June 2008 and May 2010, 972 open heart surgery operations were performed in our department. In this group there were 41 patients who had severe atherosclerotic plaques in the aorta (porcelain aorta), and 9 of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…29,30,60 Hunold et al 64 found severe calcification of the thoracic aorta in 13 of 1812 patients (0.7%) with known or suspected CAD who underwent an EBCT scan. The prevalence of PA was found to be 7.5% in patients evaluated for AS, 7 between 1.2% and 13.6% in patients undergoing valvular or coronary revascularization surgeries, 8,14,[65][66][67][68] and between 5% and 33% in the patients undergoing TAVR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…29,30,60 Hunold et al 64 found severe calcification of the thoracic aorta in 13 of 1812 patients (0.7%) with known or suspected CAD who underwent an EBCT scan. The prevalence of PA was found to be 7.5% in patients evaluated for AS, 7 between 1.2% and 13.6% in patients undergoing valvular or coronary revascularization surgeries, 8,14,[65][66][67][68] and between 5% and 33% in the patients undergoing TAVR.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, if the aorta is not totally calcified and a noncalcified area is ascertained by epiaortic scanning and palpation, a "clampless" proximal anastomosis can be performed using a Heartstring device. 8,59,68 Lev-Ran et al 59 retrospectively compared the results of coronary revascularization between cardiopulmonary bypass with femoral artery cannulation in 15 patients and off-pump CABG in 41 patients with PA. There was only 1 case of perioperative mortality (2.4%) and there were no cases of perioperative stroke or transient ischemic attack in the off-pump CABG group.…”
Section: Pa and Cardiac Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…2 Furthermore, coronary artery bypass on a beating heart (off-pump surgery) can be performed safely in patients with a severely calcified (porcelain) ascending aorta, 3 in addition to the use of ITA grafts associated with the no-touch aorta technique and placing proximal anastomoses on the ITA, which are useful strategies to reduce the perioperative risk of cerebrovascular events due to atheroembolism. 4 Unilateral Dilated Fixed Pupil After Thoracic Surgery: Need for Concern?…”
mentioning
confidence: 99%
“…Pilocarpine will constrict the pupil in nonpharmacologic etiologies but there will be no response if the mydriasis is due to a pharmacologic agent. 1,4,5 Pupillary dilation not resolving even after 48 hours of discontinuation of the drugs also may suggest the requirement…”
mentioning
confidence: 99%